Law and the Citizen - Sarat, Austin (Studies in Law, Politics, and Society Ser., 2020)
This volume brings together an international and interdisciplinary array of scholars to explore issues around citizenship and law. With chapters on different elements of the relationship between law and citizenship, the volume makes a key contribution to the field and is essential reading for legal scholars.